METODE HOMESCHOOLING, MODEL ALTERNATIF PENDIDIKAN ANAK USIA DINI DI MASYARAKAT - Wartha, Ida Bagus Nyoman (Jurnal Santiaji Pendidikan (JSP), 2011)
Learning is necessity, not just for children, but also for all people required to get an education. Bresekamp, an expert on developmental psychology (1997:97), reveals that administration in early children education is recognized as a very important period in building human resources and the danger comes once this period and can not be repeated again, so that stimulation can be started with an education that can be absolutely necessary. Homeschooling is a process that can be done by any parents who love and care their children. Any educational background or job does not preclude parents to make educational homeschooling. It needs commitment, willingness to learn, and work hard. Homeschooling is not an easy thing, but it can be carried out because it has millions of parents who do it for their children Homeschooling families who apply this system, must see that this model has a great opportunity to teach the habit of looking for any information for their children’s education needs which focus on skills that are loaded with the latest information. Homeschooling can be an alternative method for children’s education in the early age, in addition to its application implemented in home environment, kids can directly interact and apply their knowledge in the real world, and at the same time, the children can immediately get explanation or correction when making the mistake. In addition to be able to carry out the methods of homeschooling, parents should be able to spend their time for their children and be creative and innovative so as to be able to attract and interact in knowing the curiosity of the children.